Peran Moderasi Sanksi Pajak dalam Pengaruh Love of Money, Machiavellian, Tarif Pajak, Pemahaman Perpajakan dan Self Assessment System Terhadap Tax Evasion - Shofia Fatimatuz Zahro’; Marhaendra Kusuma; Muhammad Alfa niam; Srikalimah Srikalimah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of love of money (X1), Machiavellian (X2), tax rates (X3), understanding of taxation (X4) and self-assessment system (X5) on tax evasion (Y) and tax sanctions (Z) as moderating variable, for individual taxpayers who are active and registered at the Kediri Primary Tax Office in 2023. The analysis technique in this study uses multiple linear regression analysis with moderating variables (MRA). The sampling technique uses random sampling and determines the number of samples of 100 WPOP obtained from the calculation of the Slovin Formula. The results of the study show that love of money, Machiavellianism, tax rates, understanding of taxation and the self-assessment system have a positive and significant effect on tax evasion. The test results of the variable moderation of tax sanctions are able to weaken the Machiavellian influence, tax rates and understanding of taxation on tax evasion actions, while the role of moderation of tax sanctions in the influence of love of money and self assessment systems on tax evasion actions is able to strengthen.